'The violence we live in': reading and experiencing violence in the field. Issue 2 (2nd January 2017) - Moghnieh, Lamia
ABSTRACT: Anthropological literature on ethnographic experiences of violence, like Ethnographies under Fire (Nordstrom & Robben, 1995. Fieldwork under Fire: Contemporary Studies of Violence and Culture . Berkeley: University of California Press) and Violence: Ethnographic Encounters (Ghassem-Fachandi, 2009. Violence: Ethnographic Encounters . Oxford: Berg), has mostly approached violence as either a force of destruction and rupture located at the end of politics and the social, or as a thing encountered during fieldwork that alienates the researcher from her object of study. Rarely does this fieldwork literature speak of how we can ethnographically capture violence not only as destructive, but also as a social life force (Thiranagama, 2011. In My Mother's House: Civil War in Sri Lanka . Philadelphia: University of Pennsylvania Press) that transforms and reconfigures subjectivities, suffering and place. How can ethnographies investigate the social and political possibilities that emerge from violence, while also accounting for its detrimental effects? Based on my research on the humanitarian knowledge practices of violence, trauma and the politics of suffering in Lebanon, the author explores in this article what an ethnography of living-in-violence can offer to our understanding and conceptualization of violence. The author shows the need to theorize critically the experience of living-in-violence in relation to dominant portrayals of violence as an experience of encounter. Reading violence in conflict sites is the work of experts who encounter violence 'in the field' (like humanitarian workers, ethnographers, psychologists and military personnel/fighters) and communities who live in violence. However, the work of reading violence in the everyday serves to delineate the conditions of possibility for liveability and precariousness. It also serves to normalize experiences of certain kinds of violence while others are produced as traumatic. Drawing from several ethnographic moments and writings on violence, the author asks in this article: How can ethnography capture the experience of living-in-violence? And what is its analytical importance? How can an ethnography of reading violence help us make sense of different experiences of violence as distinct forms of knowledge production?